Analisis Unsur Hara Makro N, P, K dan Mg Pupuk Organik Cair dari Bahan Batang dan Kulit Buah Pisang - Didik Hermawan; Widya Lestari; Yusmaidar Sepriani; Siti Hartati Yusida Saragih (JURNAL MAHASISWA AGROTEKNOLOGI (JMATEK), 2023)
Analysis of Macro Nutrients N,P,K And Mg Liquid Organic Fertilizer From Banana Stem And Peel Material. This research was conducted on Jl. Sempurna kelurahan Bakaran Batu Kec, Rantau Selatan Kab, Labuhanbatu Sumatera Utara, and analyzed at PT SOCFIN INDONESIA Kebun Bangun Bandar SEED Production Desa Martebing Kec. Dolok Masihul Kab. Serdang Bedagai. This study aims to determine the nutrient content of liquid organic fertilizer from banana stems and peels using coconut water, rice washing water and a mixture of coconut water and rice water. This research was conducted on February 11 to February 26, 2021. The research method used was experimental laboratory. The stages of this research include finding sources of material regarding the fermentation process of liquid organic fertilizer from banana plant waste looking for similar research, determining variables, experiment preparation, conducting experiments, analyzing parameters N, P, K and Mg. The data obtained are made into tables and graphs of the results of the analysis, and draw conclusions. The results of the analysis of nutrients with the highest content in liquid organic fertilizer 1 with coconut water are potassium nutrients of 3.26%, the results of the analysis of the highest nutrients in liquid organic fertilizer 2 with fallow washing water are potassium nutrients of 2.29% and fertilizers liquid organic 3 with water mixed with rice water and coconut water, the highest nutrient content is potassium at 3.04%. Keywords : Nutrient Content of N, P, K and Mg, Banana Waste